Detection of Concordance between Transcriptional Levels of GPCRs and Receptor-Activity-Modifying Proteins - Barbash, Shahar; Persson, Torbjörn; Lorenzen, Emily; Kazmi, Manija A.; Huber, Thomas; Sakmar, Thomas P. (iScience, 2019)
A recent phylogenetic analysis showed global co-evolution of G protein-coupled receptors (GPCRs) and receptor-activity-modifying proteins (RAMPs) suggesting global interactions between these two protein families. Experimental validation of these findings is challenging because in humans whereas there are only three genes encoding RAMPs, there are about 800 genes encoding GPCRs. Here, we report an experimental approach to evaluate GPCR-RAMP interactions. As a proof-of-concept experiment, we over-expressed RAMP2 in HEK293T cells and evaluated the effect on the transcriptional levels of 14 representative GPCRs that were selected based on the earlier phylogenetic analysis. We utilized a multiplexed error-correcting fluorescence in situ hybridization (MERFISH) method to detect message levels for individual GPCRs in single cells. The MERFISH results showed changes in GPCR message levels with RAMP2 over-expression in a concordant pattern that was predicted by the earlier phylogenetic analysis. These results provide additional evidence that GPCR-RAMP interactions are more widespread than previously appreciated and that these interactions have functional consequences. [Display omitted] •A multiplexed fluorescence in situ hybridization (MERFISH) approach was used•GPCR and RAMP2 transcriptional levels were measured in single cells•Transcriptional levels were correlated as predicted by phylogenetic analysis•Results suggest that RAMPs and GPCRs globally interact with functional consequences Biological Sciences; Cell Biology; Molecular Biology